POST VITRECTOMY RETINAL REDETACHMENT AND VISUAL ACUITY DIFFERENCE WITH AND WITHOUT SCLERAL BUCKLING IN RHEGMATOGENOUS RETINAL DETACHMENT - Daivi Prakriti; Ari Andayani; Ni Made Laksmi Utari; I Gde Raka Widiana (Indonesian Vitreoretinal Society, 2026)
Introduction: Vitrectomy pars plana (VPP) either with or without scleral buckling (SB) is the definitive treatment for rhegmatogenous retinal detachment (RRD). Installation of SB with VPP is still a controversy. There has not been any conclusive evidence regarding whether VPP with SB can give a better outcome compared to VPP alone for RRD patients. This research aimed to assess the difference of retinal redetachment and visual acuity post VPP with and without SB in RRD. Methods: This observational analytic research used secondary data in the form of medical records from January 2019 – June 2021. Research samples are all RRD cases who has undergone VPP with or without SB in Central Surgical Installation of Sanglah General Hospital Denpasar who fulfill inclusion and exclusion criteria, taken consecutively. A total of 60 samples were obtained. Data collected including age, gender, preoperative visual acuity, onset, RD extension, retinal break location, presence of PVR, macular status, type of tamponade as well as visual acuity and retinal redetachment post-surgery on the first week, first month and second month. Analysis was done using SPSS version 21. Result: The results showed no significant difference in redetachment risk on multivariate analysis of the two groups. Age, PVR, and macular status contributed to redetachment risk. Multivariate analysis found significant difference in visual acuity of both groups on the second month post-surgery. Onset, macular status, and extent of RD also influences visual acuity prognosis. Conclusion: This research cannot provide adequate evidence that VPP with SB can give better outcome compared to VPP alone. Although multivariate analysis found better visual outcome in patients treated with VPP with SB, this result was related to onset, macular status and the extent of RD. The disadvantages of VPP with SB involved longer surgery time, post surgical edema and pain. Further research with longer follow up duration, blinding and randomization or RCT can be done for better evidence to determine which is more superior.